Risk Factors for Non-O157 Shiga Toxin–Producing Escherichia coli Infections, United States - Ellyn P. Marder; Zhaohui Cui; Beau B. Bruce; LaTonia Clay Richardson; Michelle M. Boyle; Paul R. Cieslak; Nicole Comstock; Sarah Lathrop; Katie Garman; Suzanne McGuire; Danyel Olson; Duc J. Vugia; et al. (Emerging Infectious Diseases, 2023)
Shiga toxin–producing Escherichia coli (STEC) causes acute diarrheal illness. To determine risk factors for non-O157 STEC infection, we enrolled 939 patients and 2,464 healthy controls in a case–control study conducted in 10 US sites. The highest population-attributable fractions for domestically acquired infections were for eating lettuce (39%), tomatoes (21%), or at a fast-food restaurant (23%). Exposures with 10%–19% population attributable fractions included eating at a table service restaurant, eating watermelon, eating chicken, pork, beef, or iceberg lettuce prepared in a restaurant, eating exotic fruit, taking acid-reducing medication, and living or working on or visiting a farm. Significant exposures with high individual-level risk (odds ratio >10) among those >1 year of age who did not travel internationally were all from farm animal environments. To markedly decrease the number of STEC-related illnesses, prevention measures should focus on decreasing contamination of produce and improving the safety of foods prepared in restaurants.